2018
DOI: 10.1155/2018/4208492
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Upper Limb in Children with Acquired Brain Injury: A Preliminary Comparative Study

Abstract: Acquired brain injuries (ABIs) can lead to a wide range of impairments, including weakness or paralysis on one side of the body known as hemiplegia. In hemiplegic patients, the rehabilitation of the upper limb skills is crucial, because the recovery has an immediate impact on patient quality of life. For this reason, several treatments were developed to flank physical therapy (PT) and improve functional recovery of the upper limbs. Among them, Constraint-Induced Movement Therapy (CIMT) and robot-aided therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Patients were evaluated before (T0) and after (T1) the intervention with the Quality of Upper Extremities Skills Test (QUEST) and the Melbourne Assessment of Unilateral Upper Limb Function [5, 16, 25], according to the evaluation protocol defined at the IRCCS E. Medea.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were evaluated before (T0) and after (T1) the intervention with the Quality of Upper Extremities Skills Test (QUEST) and the Melbourne Assessment of Unilateral Upper Limb Function [5, 16, 25], according to the evaluation protocol defined at the IRCCS E. Medea.…”
Section: Methodsmentioning
confidence: 99%
“…This device records movement parameters such as resistance, strength, coordination and range of motion and is adjustable according to the patient's condition. We found 7 clinical studies involving this device [81][82][83][84][85][86][87]. It has been used primarily for clinical rehabilitation protocols for children with CP, demonstrating a better quality of upper limb movements due to improvements of QUEST and MAAULF scales at the end of the training [81][82][83].…”
Section: Robotic Protocols For Upper Limb Rehabilitationmentioning
confidence: 99%
“…Due to this different responses to the same treatment, authors suggested the need to differentiate the rehabilitative protocol according to the neurological disorders. In another study, Beretta et al [86] trained children with ABI with different approaches: CIMT (Constraint-Induced Movement Therapy), PT (physical therapy), Armeo Spring with the purpose to characterize the possible different outcomes. It turned out that CIMT treatment emerged as the most effective in improving the proximal movements, specifically at the shoulder joints, PT promoted an improvement in the distal movements and increased the speed and fluidity of fingers, while the Armeo Spring therapy elicited improvements in shoulder RoM in abduction/adduction but it worsened performance in flexion/extension.…”
Section: Robotic Protocols For Upper Limb Rehabilitationmentioning
confidence: 99%
“…The effects of robotic therapies were observed as well, in terms of smoothness, accuracy, and velocity of motor performance, suggesting the possibility of promoting neuroplasticity at both shoulder and elbow level [14]. In a recent study [15] combined constrained induced therapy and robotic therapy demonstrating therapeutic effects on proximal and distal kinematics on children. Kinematics is also used to evaluate motor control capability and smoothness, often coupled with standard clinical tests [16].…”
Section: Introductionmentioning
confidence: 95%